2006
DOI: 10.1093/deafed/enl006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Evaluation of Linguistic Input Support to a Prelingually Deaf Child With Cued Speech: A Case Study

Abstract: This paper studies the linguistic input attended by a deaf child exposed to cued speech (CS) in the final part of her prelinguistic period (18-24 months). Subjects are the child, her mother, and her therapist. Analyses have provided data about the quantity of input directed to the child (oral input, more than 1,000 words per half-an-hour session; cued ratio, more than 60% of oral input; and attended ratio, more than 55% of oral input), its linguistic quality (lexical variety, grammatical complexity, etc.), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition, even though they might wear hearing aids they do not develop a ''listening attitude''. It is difficult to convert from a visual (and spatial) to an auditory (and temporal) communication system [25][26][27]. However, this is not impossible, as we report here one of such exceptional cases, a former exclusive sign language user, who became able to convert to the oral mode only.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, even though they might wear hearing aids they do not develop a ''listening attitude''. It is difficult to convert from a visual (and spatial) to an auditory (and temporal) communication system [25][26][27]. However, this is not impossible, as we report here one of such exceptional cases, a former exclusive sign language user, who became able to convert to the oral mode only.…”
Section: Discussionmentioning
confidence: 94%
“…Seven studies had more than 21 participants 13,[29][30][31][32][33][34] , in which three publications 29,31,33 had hearing participants as direct target of the interventions (e.g., parents, teachers and CI users caretakers) aiming to evaluate its indirect effects on deaf children and CI users' rehabilitation. Two studies were characterized as case studies and only one individual participated of each 35,36 .…”
mentioning
confidence: 99%
“…Table 1 shows the description of the participants, as well as the difficulties to identify the participant's diagnostics. Most of the studies (13 publications) among those that provided directly or indirectly information about when the hearing loss occurred (some studies provide only the child's age at the time of diagnosis or at the time of implantation) -if pre-lingual or post-lingual -had pre-lingual deaf children as participants 13,14,[16][17][18][19][20][21]24,26,30,35,36 . Only one study explicitly reported the participation of post-lingual deaf individuals 26 .…”
mentioning
confidence: 99%
See 2 more Smart Citations